The Synergy of Arts, Neuroscience, and Islam in Early Childhood Learning in Yogyakarta - Suyadi, Suyadi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
AbstractArts in Islam is an expression of tawheed (oneness of God) and prophetic, which is in neuroscience stated as able to activate the brain, affect emotions, and improve social skills, motivation, cultural awareness, and aesthetic appreciation. The purpose of this research is to analyze the synergy of arts and science in early childhood learning at three Early Childhood Education institutions in Yogyakarta, which has a variety of Islamic styles. The approach of this research was qualitative descriptive. Data collection techniques were conducted by observation, in-depth interviews, and documentation. The data analysis technique was done in descriptive, interpretative, and comparative with reference to neuroscience learning theory. The results showed that what makes art always controversial with the Islamic teachings is not in essence, but on other things that are often expressed unethically. Arts in Islamic education of early childhood are the religious arts that empathic and full-meaning, thus not only in accordance with Islamic teachings but becomes the basic needs of every people. The synergy of arts and science in early childhood learning can improve learning creativity.AbstrakSeni dalam Islam merupakan ekspresi tauhid dan profetik, yang dalam neurosains dinyatakan mampu mengaktivasi otak, mempengaruhi emosi, meningkatkan keterampilan sosial, motivasi, kesadaran budaya dan apresiasi estetika. Tujuan penelitian ini adalah menganalisis sinergi seni dan sains dalam pembelajaran anak usia dini pada tiga lembaga PIAUD di Yogyakarta yang memiliki corak keisalaman beragam. Pendekatan penelitian ini adalah kualitatif deskriptif. Teknik pengumpulan data dilakukan dengan observasi, wawancara mendalam dan dokumentasi. Teknik anailis data dilakukan secara deskriptif, interpretatif dan komparatif dengan mengacu teori pembelajaran neurosains. Hasil penelitian menunjukkan bahwa yang menjadikan seni selalu kontroversi dengan ajaran Islam bukan pada esensinya, melainkan pada hal-hal lain yang sering kali diekspresikan secara tidak etis. Seni dalam pendidikan Islam anak usia dini adalah seni religi yang empatik dan meaning fullness sehingga tidak saja sesuai dengan ajaran Islam melainkan menjadi kebutuhan asasi setiap orang. Sinergi seni dan sains dalam pembelajaran anak usia dini dapat meningkatkan kreatifitas belajar. How to Cite : Suyadi. (2018). The Synergy of Arts, Neuroscience, and Islam in Early Childhood Learning in Yogyakarta. TARBIYA: Journal of Education in Muslim Society, 5(1), 42-54. doi:10.15408/tjems.v5i1.7934.